(untitled) - S James Booth (Cambridge, Massachusetts, 1996)
The book provides complete learning resource for medical microbiology; covers basic concepts and clinical conditions; includes pathogenic bacteriology, virology, mycology, immunology, and parasitology; offers perfect review for board exams; and also presents detailed explanations of correct and incorrect answers
Keywords: medical microbiology - examinations, questions, etc